Survival after lung transplantation in recipients with alpha‐1‐antitrypsin deficiency compared to other forms of chronic obstructive pulmonary disease: a national cohort study. (12th September 2017) - Gulack, Brian C.; Mulvihill, Michael S.; Ganapathi, Asvin M.; Speicher, Paul J.; Chery, Godefroy; Snyder, Laurie D.; Davis, R. Duane; Hartwig, Matthew G.
Summary: Alpha‐1‐antitrypsin deficiency (AATD) is grouped with chronic obstructive pulmonary disease (COPD); however, this may not be appropriate. This study assessed whether AATD confers a different prognosis than COPD following lung transplantation. We employed the United Network for Organ Sharing (UNOS) database, grouping patients by diagnoses of AATD or COPD. Kaplan–Meier methods and Cox modeling were performed to determine the association of diagnosis and overall survival. Of 9569 patients, 1394 (14.6%) had a diagnosis of AATD. Patients with AATD who received a single‐lung transplant had reduced 1‐year survival [adjusted hazard ratio (AHR): 1.68, 95% CI: 1.26, 2.23]. Among patients who received a bilateral lung transplant, there was no significant difference in survival by diagnosis (AHR for AATD as compared to COPD: 0.96, 95% CI: 0.82, 1.12). After the implementation of the lung allocation score (LAS), there was no significant difference in survival among patients who received a single (AHR: 1.15, 95% CI: 0.69, 1.95) or bilateral (AHR: 0.99, 95% CI: 0.73, 1.34) lung transplant by diagnosis. Lung transplantation is increasingly employed in the care of the patient with COPD. Although recipients undergoing LTX for AATD are at increased risk of both acute rejection and airway dehiscence post‐transplant, in the post‐LAS era, survival rates are similar for recipients with AATD in comparison with COPD.